2020
DOI: 10.35219/awet.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Structure and Fracture Behavior of Additive Manufactured FFF-ABS Specimens

Abstract: The Fused Filament Fabrication (FFF) method is one of the most important additive manufacturing (AM) technologies. This technology is used today with various kinds of thermoplastic materials, including ABS. The present study deals with the flexural strength and axial deflection of ABS specimens versus relative density, to observe the influence of build-orientations, build model and microscopic level defects of these properties. In this study, the mechanical and structural characterization of AM-FFF ABS materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…properties of the tilted FFF-ABS specimens (Fig.3), where  r (%) is the relative density,  (mm) is the axial deflection, and  (MPa) is the flexural strength properties. The properties of the 90° (upright) specimens were reported by Gewelber et al (2020)[3] …”
mentioning
confidence: 81%
See 2 more Smart Citations
“…properties of the tilted FFF-ABS specimens (Fig.3), where  r (%) is the relative density,  (mm) is the axial deflection, and  (MPa) is the flexural strength properties. The properties of the 90° (upright) specimens were reported by Gewelber et al (2020)[3] …”
mentioning
confidence: 81%
“…The chosen 3D-printed specimen is a simple rectangular beam with specified geometry and dimensions according to ASTM D790 and ISO 178. The properties of the 90° (upright) specimens used in the current paper are taken from our previous ongoing study as reported by Gewelber et al ( 2020) [3]. The specimens were produced using the solid mode filling mode with a single outer raster line defining the layer's perimeter; each layer is composed of individual raster lines whose orientation varies between the layer at -45°/+45° (crisscross) according to the print strategy; the crisscross strategy is the most frequently employed as the default raster pattern in most FFF extruders.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Fused filament fabrication (FFF) is a commonly used additive manufacturing (AM) process, based on extrusion and mainly applied in rapid prototyping [1] - [11]. With the development of advanced materials and technology, the AM-FFF technique is shifting from manufacturing prototypes to the production of industrial end products.…”
Section: Introuctionmentioning
confidence: 99%
“…With the development of advanced materials and technology, the AM-FFF technique is shifting from manufacturing prototypes to the production of industrial end products. Mechanical properties need to be studied in detail to further bring the FFF technique into volume production in order to fabricate functional parts for new applications in many sectors of biomedical engineering, aerospace, civil engineering, and robotics [1] - [10]. For example, in the automotive industry, the AM-FFF method is used to print fixtures and jigs as well as prototypes for testing [2].…”
Section: Introuctionmentioning
confidence: 99%